Training on Issue and Crisis Management for Village Government Officials of Eureunpalay Village Cibalong Tasikmalaya - Yudha Pradhana; Vivitri Endah Andriani; Amadhea Zahra Febriani; Tasya Nur’aida; Ester Berliana; Mohammad Daffa Roihandro (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The Issue and Crisis Management Training conducted for village government officials in Eureunpalay Village, Cibalong Subdistrict, Tasikmalaya, aimed to enhance effective communication skills in handling crisis situations. The training was attended by 20 participants, consisting of village apparatus and local community leaders. The initiative was motivated by the lack of understanding and practical skills among village officials in managing various issues and crises that may arise within the community, including natural disasters, social conflicts, and other emergency situations. Data collection methods included direct observation and open-ended interviews with participants to assess the development of their capacities throughout the training. The indicators of program success comprised: (1) increased participants' understanding of crisis communication techniques; (2) improved ability to apply vocal control, body language, and eye contact when speaking publicly; and (3) enhanced confidence in conveying messages during emergencies. The training outcomes showed a significant improvement in participants’ preparedness to face crisis situations, both in terms of technical communication skills and psychological readiness under pressure. The implications of these outcomes suggest that such training programs are a critical strategy in strengthening the capacity of village government officials, particularly in building effective communication during crises. Therefore, this initiative is recommended to be continued and scaled up to other villages as part of a broader effort to enhance local governance resilience.